Significant reduction of ischemia‐reperfusion cell death in mouse myocardial infarcts using the immediate‐acting PrC‐210 ROS‐scavenger. Issue 4 (12th July 2019) - Hacker, Timothy A.; Diarra, Gaoussou; Fahl, Bryan L.; Back, Susan; Kaufmann, Erin; Fahl, William E.
Abstract: Managing myocardial infarction (MI) to reduce cardiac cell death relies primarily on timely reperfusion of the affected coronary site, but reperfusion itself induces cell death through a toxic, ROS‐mediated process. In this study, we determined whether the PrC‐210 aminothiol ROS‐scavenger could prevent ROS‐induced damage in post‐MI hearts. In a series of both in vitro and in vivo experiments, we show that: (a) in vitro, PrC‐210 was the most potent and effective ROS‐scavenger when functionally compared to eight of the most commonly studied antioxidants in the MI literature, (b) in vitro PrC‐210 ROS‐scavenging efficacy was both immediate (seconds) and long‐lasting (hours), which would make it effective in both (1) real‐time ( seconds ), as post‐MI or cardiac surgery hearts are reperfused with PrC‐210‐containing blood, and (2) long‐term ( hour s), as hearts are bathed with systemic PrC‐210 after MI or surgery, (c) systemic PrC‐210 caused a significant 36% reduction of mouse cardiac muscle death following a 45‐minute cardiac IR insult; in a striking coincidence, the PrC‐210 36% reduction in cardiac muscle death equals the 36% of the MI‐induced cardiac cell death estimated 6 years ago by Ovize and colleagues to result from "reperfusion injury, " (d) hearts in PrC‐210‐treated mice performed better than controls after heart attacks when functionally analyzed using echocardiography, and (e) the PrC‐210 ROS‐scavenging mechanism of action was corroborated by its ability to prevent >85% of the direct, H2 O2 ‐induced killing of neonate cardiomyocytes in cell culture. PrC‐210 does not cause the nausea, emesis, nor hypotension that preclude clinical use of the WR‐1065/amifostine aminothiol. PrC‐210 is a highly effective ROS‐scavenger that significantly reduces IR injury‐associated cardiac cell death.